Keterbatasan dan Peluang Penelitian Bimbingan Konseling di Sekolah Dasar Berbasis Teknologi: Analisis Kesenjangan - Jasuma, Nelly Herawati (STKIP PGRI Bandar Lampung, 2025)
This study aims to identify, evaluate, and synthesize the trends and recent research findings on technology implementation in guidance counseling services at the elementary school level. Employing a systematic review of journal articles and conference proceedings from 2015 to 2024, the study finds that the use of technology, such as mobile applications, web platforms, and multimedia, enhances the accessibility, effectiveness, and personalization of guidance counseling for elementary students. Although technology use in counseling services has shown positive development, significant methodological limitations remain (small samples, quasi-experimental design, lack of control groups), along with insufficient exploration of crucial topics like crisis counseling and career guidance, and a lack of cross-cultural research especially in Indonesia and other developing countries. Future research is recommended to employ stronger designs (randomized controlled trials), explore less-studied topics, and utilize cross-cultural approaches to ensure technology-based counseling is relevant and effective for students in diverse environments.